Evidence of demand factors in the determination of the labor market intermittency penalty - Julie L. Hotchkiss; M. Melinda Pitts (Federal Reserve Bank of Atlanta, 2007)
The purpose of this paper is to determine whether any empirical evidence exists for the contribution of employer, or demand-side, determinants of the labor market intermittency penalty. The documented negative relationship between the size of the penalty and labor market strength is interpreted as evidence that labor market intermittency is viewed as an undesirable characteristic that employers penalize more severely when the labor market is weak.
Keywords: J31; J22; 330; intermittent labor supply; time allocation; wage determination